The Influence of Brand Image, Brand Trust and Product Packaging Information on Purchasing Decisions - Wijaya, Angga Pandu; Annisa, Intan Tri (Jurnal Analisis Bisnis Ekonomi, 2020)
Consumer health awareness has increased recently, this is evidenced by the desire to consume herbal products. Today’s packaged colds jamu become a practical alternative for consumers to continue taking herbal medicines that are easy to obtain. This study aims to examine the influence of brand image, brand trust and product packaging information on the purchase decision of packaged cold herbs. This quantitative study applied purposive random sampling by using PLS-SEM 3.0 as statistic tools with questionnaire filled by 100 respondents. This article delivers a substantial effect to significant variables in purchasing decision. The results show that brand image does not directly influence purchasing decisions, but is fully mediated by brand trust. On the other hand, packaging information has a positive and significant effect on purchasing decisions.